Inflammatory myofibroblastic bladder tumor with divergent behavior in a patient with spinal cord injury. Issue 4 (29th May 2019) - Tsuboi, Ichiro; Maruyama, Yuki; Sadahira, Takuya; Wada, Koichiro; Ando, Nobuyoshi; Mitsui, Yosuke; Nishiyama, Yasuhiro; Arata, Ryoji; Araki, Motoo; Nasu, Yasutomo; Ono, Noriaki
Abstract : Introduction: An inflammatory myofibroblastic tumor of the bladder is rare. Some urothelial carcinoma with sarcomatoid changes may mimic an inflammatory myofibroblastic tumor. Case presentation: A 76‐year‐old man with indwelling urinary catheters because of a spinal cord injury presented with gross hematuria. Transurethral electrocoagulation and a resection were performed. A T2‐weighted magnetic resonance imaging showed a tumor and hematoma in the bladder diverticulum that pathologically resembled an inflammatory myofibroblastic tumor. This lesion was then removed en bloc by partial cystectomy. Histology showed a squamous cell carcinoma with sarcomatoid changes. After 4 months, a computed tomography showed the lesion had expanded outside the skin adjacent to the bladder. Conclusion: Some cases of inflammatory myofibroblastic tumors have a malignant course. Urologists therefore need to be aware of the possibility of rare cases of malignant bladder myofibroblasts.